Ответы и объяснения

2014-02-21T17:51:30+00:00
3а-(b+15a²)/(5a-2)+5a/(2-5a)=3a-(b+15a²-5a):(5a-2)=(3a(5a-2)-(b+15a²-5a)):(5a-2)=(15a²-6a-b-15a²+5a):(5a-2)=(-a-b):(5a-2)
-(-0,8)-16  :  5*(-0,8)-2=-15,2:(-6)=76/5*1/6=38/15=2 8/15

(m-6n²)/(2n-1)+3n-2n/(1-2n)=(m-6n²+3n(2n-1)+2n) : (2n-1)=(m-6n²+6n²-3n+2n) : (2n-1)=(m-n)/(2n-1)
(12+3)/(2*(-3)-1)=15/(-7)=-2 1/7

( (3х-10у²)+5у(2у-3)-(2х-13у) ) :(2у-3)=( 3х-10у²+10у²-15у-2х+13у ) :(2у-3)= ( х-12у) :(2у-3)
(14-12(-3,5)) : (2(-3,5)-3)=56/10=5,6

((m²-n)-m(m-7)+6m) : (m-7)=(m²-n-m²-7m+6m) : (m-7)=(-n-m) : (m-7)
(-(-4)-2):(2-7)=2/(-5)=-2/5

Если не понятно, спрашивай.